Deviance and Control theory, research, and social policy - Little, Craig B. (F.E. Peacock, 1989)
Contents of this book consist of explanations of devience and control, heterosexual deviance, homosexuality, mental disorders, sucide, alcohol and other drugs, familyviolence, street crime and delinquency...